Point‐of‐Care Ultrasound as a Component of Preparticipation Screening of Athletes: A Systematic Review. (12th May 2019) - Cassels, Michael; Moulson, Nathaniel; Regan, Jackie; MacDonald, Mackenzie; Isserow, Saul; Johri, Amer M.; McKinney, James
Abstract : This review examined whether the addition of point‐of‐care ultrasound (POCUS) to electrocardiography (ECG)‐inclusive preparticipation screening strategies has the potential to reduce false‐positive results and detect diseases associated with sudden cardiac death that may not be identified through current modalities. Five studies, representing 2646 athletes, demonstrated that ECG‐inclusive preparticipation screening strategies resulted in positive results in 19.9% of the cohort. With the addition of POCUS, positive results were reduced to 4.9%, and 1 additional condition potentially associated with sudden cardiac death was identified. The magnitude of positive results with POCUS may be reduced if current ECG criteria were applied.